2014
DOI: 10.1177/1355819614527439
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organisational resources and eligibility issues on transition from child and adolescent to adult mental health services

Abstract: A mutual lack of understanding of services and structures together with restrictive eligibility criteria exacerbated by perceived lack of resources can impact negatively on the transition between CAMHS and AMHS, disrupting continuity of care for young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 17 publications
3
66
0
Order By: Relevance
“…All studies explored experiences of ADHD‐specific mental health populations, except Belling et al. (). The aims of two studies (Belling et al., ; Wong et al., ) differed from those of this review, so only relevant aspects were extracted.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies explored experiences of ADHD‐specific mental health populations, except Belling et al. (). The aims of two studies (Belling et al., ; Wong et al., ) differed from those of this review, so only relevant aspects were extracted.…”
Section: Resultsmentioning
confidence: 99%
“…Several respondents discussed negative impacts of not knowing what to expect,
A bit vague what's available. (Nurse, CAMHS) (Belling et al., )When she gets to 18 is there gonna be somebody there that can talk to us and talk to her? … We just don't know.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is now a shift towards CAMHS continuing to provide care for patients up to 18 years of age regardless of school status. It has been suggested that AMHS are often too rigid in their age criteria for transition, with reports of refusals to consider transition until the individual reaches the age of 18 [3]. To further complicate issues it is reported anecdotally that whatever the technical cut-off age may be, many paediatric and CAMHS teams continue to see young people well past this age, due to the difficulties in transferring care to adult services [33].…”
Section: Introductionmentioning
confidence: 99%